2018
DOI: 10.1016/j.celrep.2018.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Control Mechanisms for DNA Replication and Cell Division in E. coli

Abstract: Understanding the classic problem of how single E. coli cells coordinate cell division with genome replication would open the way to addressing cellcycle progression at the single-cell level. Recent studies produced new data, but the contrast in their conclusions and proposed mechanisms makes the emerging picture fragmented and unclear. Here, we re-evaluate available data and models, including generalizations based on the same assumptions. We show that although they provide useful insights, none of the propose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 40 publications
6
73
1
1
Order By: Relevance
“…However, as can be seen in Figure 2A , we observe that the initiation length L i and birth length L b are clearly correlated in all conditions, rejecting the initiation mass model. The absence of an initiation mass has been noted recently elsewhere ( Micali et al, 2018a). It should be noted, however, that even though the single-cell fluctuations show that initiation is unlikely to be triggered by a critical volume per origin, one may still investigate to what extent the average volume per origin of replication is held constant across different growth conditions ( Si et al, 2017 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…However, as can be seen in Figure 2A , we observe that the initiation length L i and birth length L b are clearly correlated in all conditions, rejecting the initiation mass model. The absence of an initiation mass has been noted recently elsewhere ( Micali et al, 2018a). It should be noted, however, that even though the single-cell fluctuations show that initiation is unlikely to be triggered by a critical volume per origin, one may still investigate to what extent the average volume per origin of replication is held constant across different growth conditions ( Si et al, 2017 ).…”
Section: Resultssupporting
confidence: 55%
“…Thanks to experimental techniques like the one used here, models of bacterial cell cycle regulation dating back from the 1960’s have been recently re-examined in detail in several studies Wallden et al (2016); Si et al (2017); Micali et al (2018a); Ho and Amir (2015); Adiciptaningrum et al (2015); Logsdon et al (2017); Eun et al (2018); Tanouchi et al (2015); Campos et al (2014) . As much as these new data have been useful in shedding light on bacterial physiology regulation mechanism such as the adder, they have also revealed that multiple models are capable of reproducing in large parts experimental data, mainly as a consequence of the correlations existing between measurable cell cycle parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two processes contribute to the determination of individual bacterial cell shape: growth and division. While the relationship between bacterial size control and the timing of cell division is being thoroughly investigated [7, 8, 9], the problem of how single microbial cells achieve shape homeostasis while growing between two successive divisions is comparatively less explored [10, 11, 12, 13], and can be – to some extent – factored out from that of regulation of cell division. In particular, the relationship between cell growth and shape control has to depend on the differential biosynthesis of cellular mass (volume) and surface-specific “building blocks” [14].…”
Section: Introductionmentioning
confidence: 99%
“…9, Supplementary Models 6 ). As ‘rate maintenance’ has been used to support the link between chromosome replication and cell division 38 , a more complete model is necessary to take into account the direct influence of chromosome events on cell division 10,11 .…”
mentioning
confidence: 99%